2010
DOI: 10.1007/s11244-010-9567-8
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration of Fermented Isobutanol for the Production of Renewable Chemicals and Fuels

Abstract: Fermented 2-methyl-1-propanol (isobutanol) can be used directly as a biofuel or can be catalytically dehydrated to 2-methylpropene (isobutylene), which serves as a platform molecule for synthesizing other fuels or chemicals. The dehydration reaction was studied over alumina catalysts to determine the impact of process conditions and model compound impurities from fermentation. No significant impurity effects were observed over short (8 h) timescales and dehydration was demonstrated at high conversion and with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 16 publications
2
61
0
1
Order By: Relevance
“…Iso-butanol produced from a process such as Escherichia coli fermentation is dehydrated to a mixture of isobutene, n-butene (1-butene), and 2-butene (cis-2-butene and trans-2-butene) [74]. Acidic catalyst such as ZSM-5 zeolites, Y-type zeolites, and Amberlyst acidic resins can be used to catalyze a dehydration reaction, and different catalysts affect the selectivity of isobutene and the overall linear butenes [74] 1 .…”
Section: Process Descriptionmentioning
confidence: 99%
“…Iso-butanol produced from a process such as Escherichia coli fermentation is dehydrated to a mixture of isobutene, n-butene (1-butene), and 2-butene (cis-2-butene and trans-2-butene) [74]. Acidic catalyst such as ZSM-5 zeolites, Y-type zeolites, and Amberlyst acidic resins can be used to catalyze a dehydration reaction, and different catalysts affect the selectivity of isobutene and the overall linear butenes [74] 1 .…”
Section: Process Descriptionmentioning
confidence: 99%
“…Afterwards, the isobutanol undergoes dehydration for the corresponding alkene formation (isobutene), in presence of alumina. From [65] it is confirmed that high isobutylene conversion and high selectivity to isobutylene can be achieved with no significant impurity effects. The carbon chain growth is performed in the next reactor where olefins oligomerization takes place.…”
Section: Paraffins From Mixed Alcohols With Modified Methanol (Case 2)mentioning
confidence: 78%
“…Several relevant studies have proved that catalysts such alumina, Ru, Amberlyst acidic resins and ZSM-5 zeolites have an efficient effect on alcohols dehydration under high pressure [65]. Makarova et al [66] suggested a two step mechanics for n-butanol dehydration; the reaction proceeds via fast ether formation (dibutyl ether -C 8 H 18 O) and subsequent slower decomposition of ether.…”
Section: Alcohols Condensation (Guerbet Reactions)mentioning
confidence: 99%
“…9,10 Recently, commercially available biobutanol isomers, obtained from fermentable biomass-derived sugars, have been emerging as a renewable source for fuel. 11,12 Several enterprises have disclosed or announced their commercial processes for the production of biobutanols. Especially, the number of bioisobutyl alcohol producers continues to grow, which ensures availability on a large scale.…”
Section: Introductionmentioning
confidence: 99%